Analysis of surface integrity of intermetallic composite based on titanium-aluminum machined by laser cutting. (June 2023) - Boujelbene, Mohamed; Ezeddini, Sonia; Ben Said, Lotfi; Bayraktar, Emin; Alhadri, Muapper; Aich, Walid; Ghachem, Kaouther; Kolsi, Lioua
Highlights: Optimization of the laser gas assisted cutting process of intermetallic composite based on titanium-aluminum alloys. The laser output power ( P ) has the greatest effect on surface roughness results. Lower values of laser power and low to medium cutting speeds are preferred for this material in order to improve surface roughness and avoid microstructure defects. The optimal conditions obtained in this study of laser machining of Ti-Al based intermetallic composite are with 1400 W and 0.5 m/min. Abstract: Ti-Al intermetallic composite is a lightweight material with excellent mechanical properties, resistant to corrosion and oxidation, especially at high temperatures. It has the potential to be used in many industrial fields such as the replacement of nickel-based superalloy components in aircraft engines. The present paper treats the gas-assisted laser cutting of this composite material. It develops an experimental investigation on the effects of certain machining parameters namely laser output power and cutting speed on the surface integrity of cut edges. The main purpose of this experimental investigation is the optimization of the surface integrity of workpieces made of Ti-Al intermetallic composite, designed with the combination of thixoforming method and semi-solid powder metallurgy, when they are machined by laser cutting. The novelty of the present study is that the presented results demonstrated that the effect of these two parameters on the surface integrity is different to other materials, the best surface results are recorded at lower laser power and lower to medium cutting speeds.